The Dynamics of Digital Literacy and Its Impact on Generation Z's Social Participation in the Post-Truth Era - Ahmad Mubarok (PT. AVID MEDIA INDONESIA, 2025)
This study aims to analyze the dynamics of digital literacy and its impact on Generation Z's social participation in the post-truth era, characterized by a flood of information, disinformation, and biased public opinion. Using a qualitative approach based on a literature review, this study examines various relevant scientific sources to understand how digital literacy plays a role in shaping critical awareness and social engagement of the younger generation. The results of the study indicate that digital literacy encompasses not only technical skills but also reflective, ethical, and evaluative abilities in interpreting digital information. Generation Z has great potential as active social actors in the digital space, but is often trapped in a flow of manipulative and shallow information. Comprehensive improvements in digital literacy have been shown to influence the quality of social participation, making it more substantive, collaborative, and oriented towards social transformation. This study emphasizes the importance of integrating education, public policy, and media innovation in building a digital ecosystem that supports truth-based social participation. Thus, strengthening digital literacy is a key strategy for creating critical, ethical, and civilized digital citizens amidst the challenges of the post-truth era.